2015
DOI: 10.1007/s00109-015-1301-3
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin inhibits diabetic renal tubulointerstitial fibrosis through blocking epithelial to mesenchymal transition

Abstract: • Glucose increases renal tubular epithelial induction of vimentin, α-SMA and FSP-1. • Glucose enhances renal EMT by blocking tubular epithelial E-cadherin expression. • Chrysin inhibits tubular EMT-mediated tubulointerstitial fibrosis in mouse kidneys. • Chrysin restores renal tubular induction of ZO-1 and occludin downregulated in diabetic mice. • Chrysin blocks glucose-induced renal tubular cell migration with reducing MMP-2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 41 publications
0
52
0
1
Order By: Relevance
“…Urinary albumin was measured using the Albuwell M ELISA kit (Exocell, Philadelphia, PA, USA) according to a manufacturer's instructions. The 24-h urine volume in the db/db mice was 20-fold higher than that of db/m controls, whereas in chrysin-treated mice, the volume declined by ≈50% [22] . Fasting blood glucose and blood glycated hemoglobin HbA1C levels in mouse tail veins were measured every other week.…”
Section: In Vivo Animal Experimentsmentioning
confidence: 74%
See 1 more Smart Citation
“…Urinary albumin was measured using the Albuwell M ELISA kit (Exocell, Philadelphia, PA, USA) according to a manufacturer's instructions. The 24-h urine volume in the db/db mice was 20-fold higher than that of db/m controls, whereas in chrysin-treated mice, the volume declined by ≈50% [22] . Fasting blood glucose and blood glycated hemoglobin HbA1C levels in mouse tail veins were measured every other week.…”
Section: In Vivo Animal Experimentsmentioning
confidence: 74%
“…However, whether chrysin restores optimal structure and function to the glomerular epithelial podocytes in diabetic kidney remains unknown. Our previous study showed that chrysin attenuated renal tubulointerstitial fibrosis via blocking the induction of the epithelial to mesenchymal transition in renal tubular epithelial cells and in db/db mice [22] . The epithelial to mesenchymal transition and tubulointerstitial fibrosis could be considered as novel routes and potential drug targets for the future therapeutic interventions using chrysin.…”
Section: Introductionmentioning
confidence: 97%
“…Chrysin (Figure 1A) is a flavone-type flavonoid found in honey and herbs and possesses diverse pharmacological activities and multiple biological effects in the central nervous and immune systems [29,30]. Our previous study showed that the multifunctional chrysin exhibited the renoprotection by inhibiting diabetic renal tubulointerstitial fibrosis through blocking epithelial to mesenchymal transition [31]. However, whether chrysin maintains eye health in diabetes remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanistic intracellular signaling and functional effects on human endometriotic cells remain unknown. Chrysin (5,7-dihydroxyflavone) is a flavone found in natural materials, such as chamomile, passion flowers, oyster mushrooms (Pleurotus ostreatus), and honeycombs (Kang, Park, Choi, Shin, & Kang, 2015;Lim, Ryu, Bazer, Kim, & Song, 2018). Chrysin has various biological functions, including anticancer (Khoo, Chua, & Balaram, 2010), antiinflammatory (Ha, Moon, & Kim, 2010), and antiangiogenic effects (F. Yang et al, 2015).…”
Section: O R I G I N a L R E S E A R C H A R T I C L Ementioning
confidence: 99%